Lentivirus-mediated knockdown of NLK inhibits small-cell lung cancer growth and metastasis - Lv MT; Li YM; Tian X; Dai SD; Sun J; Jin GJ; Jiang SY (Dove Medical Press, 2016)
Mutian Lv,1 Yaming Li,1 Xin Tian,2 Shundong Dai,3,4 Jing Sun,5 Guojiang Jin,6 Shenyi Jiang7 1Department of Nuclear Medicine, 2Molecular Oncology Laboratory of Cancer Research Institute, The First Affiliated Hospital of China Medical University, 3Department of Pathology, The First Affiliated Hospital, College of Basic Medical Sciences of China Medical University, 4Department of Pathology, Institute of Pathology and Pathophysiology, 5Department of Immunology and Biotherapy, Liaoning Cancer Hospital and Institute, 6Department of Laboratory Medicine, 7Department of Rheumatology, The First Affiliated Hospital of China Medical University, Shenyang, People’s Republic of China Abstract: Nemo-like kinase (NLK), an evolutionarily conserved serine/threonine kinase, has been recognized as a critical regulator of various cancers. In this study, we investigated the role of NLK in human small-cell lung cancer (SCLC), which is the most aggressive form of lung cancer. NLK expression was evaluated by quantitative real-time polymerase chain reaction in 20 paired fresh SCLC tissue samples and found to be noticeably elevated in tumor tissues. Lentivirus-mediated RNAi efficiently suppressed NLK expression in NCI-H446 cells, resulting in a significant reduction in cell viability and proliferation in vitro. Moreover, knockdown of NLK led to cell cycle arrest at the S-phase via suppression of Cyclin A, CDK2, and CDC25A, which could contribute to cell growth inhibition. Furthermore, knockdown of NLK decreased the migration of NCI-H446 cells and downregulated matrix metalloproteinase 9. Treatment with NLK short hairpin RNA significantly reduced SCLC tumor growth in vivo. In conclusion, this study suggests that NLK plays an important role in the growth and metastasis of SCLC and may serve as a potential therapeutic target for the treatment of SCLC. Keywords: NLK, SCLC, RNAi, proliferation, migration